2021
DOI: 10.3390/coatings11070793
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Detonation-Spraying Parameters on the Phase Composition and Tribological Properties of Al2O3 Coatings

Abstract: Al2O3 coatings were applied on the surface of 12Ch18N10T steel by the detonation method at different degrees of filling of the detonation gun. The aim was to study the influence of technological parameters on the formation of the coating’s structure, phase composition and tribological characteristics. The degree of filling the gun with a gas mixture (C2H2/O2) varied from 53% to 68%. X-ray diffraction study showed that the content of α-Al2O3 increases depending on the degree of filling. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Consequently, the structural and phase characteristics of aluminum oxide coatings are significantly affected by the technological parameters of detonation spraying. Our previous studies [23][24][25] also confirmed that changes in parameters such as the explosion frequency and the volume filled with the gas mixture in the barrel lead to changes in the content of α-Al 2 O 3 and γ-Al 2 O 3 phases in the coatings. In our studies [23][24][25], we used α-Al 2 O 3 as a starting powder and investigated the effects of maximum parameters on a CCDS2000 detonation machine.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Consequently, the structural and phase characteristics of aluminum oxide coatings are significantly affected by the technological parameters of detonation spraying. Our previous studies [23][24][25] also confirmed that changes in parameters such as the explosion frequency and the volume filled with the gas mixture in the barrel lead to changes in the content of α-Al 2 O 3 and γ-Al 2 O 3 phases in the coatings. In our studies [23][24][25], we used α-Al 2 O 3 as a starting powder and investigated the effects of maximum parameters on a CCDS2000 detonation machine.…”
Section: Introductionsupporting
confidence: 60%
“…Our previous studies [23][24][25] also confirmed that changes in parameters such as the explosion frequency and the volume filled with the gas mixture in the barrel lead to changes in the content of α-Al 2 O 3 and γ-Al 2 O 3 phases in the coatings. In our studies [23][24][25], we used α-Al 2 O 3 as a starting powder and investigated the effects of maximum parameters on a CCDS2000 detonation machine. We found that as the blast frequency decreases, the α-Al 2 O 3 content of the coatings increases.…”
Section: Introductionsupporting
confidence: 60%
“…Our earlier studies [22][23][24] also showed that when changing the technological modes (firing frequency, barrel filling volume) of detonation spraying, the ratio of the α-Al 2 O 3 and γ-Al 2 O 3 phases changes. In these studies [22][23][24], α-Al 2 O 3 was used as the initial powder, and the maximum possible parameters (frequency of firing and barrel filling) of the CCDS-2000 detonation unit were studied using an acetylene-oxygen mixture. It was found that with a decrease in the frequency of the shot, as well as with a decrease in the volume of filling the barrel with an acetylene-oxygen mixture, α-Al 2 O 3 increases.…”
Section: Introductionmentioning
confidence: 83%
“…Therefore, the structural and phase states of aluminium oxide coatings strongly depend on the technological mode of detonation spraying [22]. Our earlier studies [22][23][24] also showed that when changing the technological modes (firing frequency, barrel filling volume) of detonation spraying, the ratio of the α-Al 2 O 3 and γ-Al 2 O 3 phases changes. In these studies [22][23][24], α-Al 2 O 3 was used as the initial powder, and the maximum possible parameters (frequency of firing and barrel filling) of the CCDS-2000 detonation unit were studied using an acetylene-oxygen mixture.…”
Section: Introductionmentioning
confidence: 84%
“…This process can lead to undesirable overheating or melting of particles and a significant increase in the substrate temperature, which limits their effective application. The DS method utilizes a pulsed regime of operation [19]. On the one hand, this provides an opportunity to reduce the above negative effects.…”
Section: Introductionmentioning
confidence: 99%